Study of anthocyanin stability derived from the fruit pulp of Melastoma malabathricum in a coating system - Aziz, N.; Nor, N.A.M.; Mohd-Adnan, A.F.; Taha, R.M.; Arof, Abdul Kariem (Emerald, 2012)
Purpose - The purpose of this paper is to evaluate the stability of anthocyanin colorant with and without ferulic acid (FA) stabilising agent in a polyvinyl alcohol (PVA) binder coating system. Design/methodology/approach - The anthocyanin colorant was extracted using methanol acidified with 0.5 trifluoroacetic acid (TEA). FA was added to improve thermal stability of the colorant. The FA added colorant was mixed with PVA to develop a coating system. To test the ability of the coating mixture to withstand heat in the liquid state, spectroscopic studies were carried out in the visible region of the electromagnetic spectrum when the liquid samples had cooled down to room temperature after being heated at 80 and 90 degrees C for 30 minutes. This procedure was repeated six times until a total heating time of 180 minutes has been accomplished. The liquid samples were also coated on glass slides, cured and then stored in different incubators at 30, 40 and 50 degrees C. The visible spectrum was taken everyday for 30 days to study the effect of storage temperature. Spectroscopic results were analysed in terms of intensity rate percentage (IRP). Findings - In the liquid state, the anthocyanin-PVA mixture without FA showed lower absorbance compared to the mixture containing FA after heating at 80 and 90 degrees C. This shows that FA can enhance the intensity of absorbance of the liquid coating mixture. The mixtures containing FA show increase in absorbance with increase in heating time. The same results are obtained for the coating on glass substrate where FA containing coatings show increase in IRP with time for all storage temperatures. Coating with 1 FA content showed better enhancement and stability. Research limitations/implications - The colour of the untreated samples quickly faded during heating and storage at different temperatures. In this study, the addition of 0.5 and 1 FA stabilised and enhanced the colour intensity at 30, 40 and 50 degrees C. Further improvements may find the mixture suitable as paint or coating materials and as nail varnish. Practical implications - The results indicate the possibility of applying the FA stabilised anthocyanin-PVA, colorant-binder composition in a coating system. Originality/value - The use of anthocyanin from M. Malabathricum as a colourant in a coating system or nail varnish is original. Anthocyanin pigments are normally used as colorant in foods.